Polyacrylamide cellulose-based hydrogel moisture generator and preparation method thereof

By preparing a polyacrylamide cellulose-based hydrogel wet generator, high current and voltage are generated by utilizing ion concentration gradients and directional migration, solving the problem of low output of existing wet generators and achieving efficient and stable wet power generation.

CN120956111APending Publication Date: 2025-11-14ANHUI AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511385330.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing wet generators have low output current and poor continuous voltage output performance, making it difficult to meet power demand and the voltage output is not high enough.

Method used

A method for preparing a polyacrylamide cellulose-based hydrogel wet generator is adopted. By using perforated zinc electrodes and laser-engraved graphene electrodes, and cross-linking a mixed solution of acrylamide, carboxylated cellulose, deionized water, lithium chloride and N,N-methylenebisacrylamide, a porous hydrogel layer is formed, which realizes ion concentration gradient and directional migration, and generates high current and voltage output.

Benefits of technology

It exhibits excellent current and voltage performance over a wide humidity range, with high current density and voltage output, enabling continuous and stable power generation. It is suitable for powering commercial electronic equipment and is both environmentally friendly and economical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120956111A_ABST
    Figure CN120956111A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of moisture power generation, in particular to a polyacrylamide cellulose-based hydrogel moisture generator and a preparation method thereof, and the preparation method comprises the following steps: punching zinc to obtain a porous zinc electrode; engraving a polyimide film to obtain a laser-induced graphene electrode; mixing acrylamide, carboxylated cellulose, deionized water and lithium chloride to obtain a mixed solution, and mixing and stirring for 30 minutes; then adding ammonium sulfate and N, N-methylene bisacrylamide; after mixing and stirring for 30 minutes, pouring the obtained solution into a silica gel mold, and putting the silica gel mold into a constant-temperature and constant-humidity box for cross-linking, so as to obtain polyacrylamide cellulose-based hydrogel; the polyacrylamide cellulose-based hydrogel moisture generator comprises a porous zinc electrode layer, a polyacrylamide cellulose-based hydrogel layer and a laser-induced graphene layer which are sequentially connected from top to bottom; the moisture generator disclosed by the invention is good in output performance in a relatively large humidity range, relatively high in current output and relatively lasting in voltage output.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wet power generation technology, specifically to a polyacrylamide cellulose-based hydrogel wet power generator and its preparation method. Background Technology

[0002] Among various clean energy sources, the energy contained in atmospheric moisture accounts for a large proportion of the total energy. Therefore, in recent years, using moisture to generate electricity has become a new solution in the context of energy shortage. As an emerging environmentally friendly technology, moisture power generation can collect the dispersed moisture energy in the environment and convert it into electrical energy by utilizing the reaction between water and the interface and the movement of ions inside the hydrogel.

[0003] Most existing wet generators utilize the water absorption properties of materials, forming a concentration gradient of ions that leads to directional ion migration and thus generates an open-circuit voltage. However, these wet generators have the following drawbacks: 1) low output current, only in the microampere range, making it difficult to meet power demand; 2) poor continuous voltage output performance; and 3) insufficient voltage output. Summary of the Invention

[0004] The purpose of this invention is to provide a polyacrylamide cellulose-based hydrogel humid generator and its preparation method. This humid generator has good output performance over a wide humidity range, with high current output and relatively long voltage output.

[0005] The objective of this invention can be achieved through the following technical solutions: A method for preparing a polyacrylamide cellulose-based hydrogel wet generator includes the following steps: A porous zinc electrode is obtained by punching holes in zinc using a puncher; Laser-induced graphene electrodes were obtained by engraving polyimide films using a laser engraving machine. Acrylamide, carboxylated cellulose, deionized water, and lithium chloride were mixed to obtain a mixed solution, and the mixture was stirred for 30 minutes. Then ammonium sulfate and NN methylenebisacrylamide were added. After stirring for 30 minutes, the resulting solution was poured into a 1cm*1cm*0.5cm silicone mold and placed in a constant temperature and humidity chamber for crosslinking to obtain polyacrylamide cellulose-based hydrogel. The porous zinc electrode layer, polyacrylamide cellulose-based hydrogel layer, and laser-induced graphene layer are then connected sequentially from top to bottom to form a polyacrylamide cellulose-based hydrogel wet generator.

[0006] As a further aspect of the present invention: the porous zinc electrode has a size of 1*1.5 cm.

[0007] As a further aspect of the present invention: the diameter of the holes is 0.5 mm, and the number of holes is 4*4.

[0008] As a further embodiment of the present invention, the mass ratio of acrylamide, carboxylated cellulose, deionized water, lithium chloride, ammonium persulfate, and N-N-methylenebisacrylamide is (4-4.5):(0.14-0.16):(14-16):(2.8-3.2):(0.13-0.14):(0.005-0.007).

[0009] As a further aspect of the present invention, the crosslinking temperature is 60°C.

[0010] As a further aspect of the present invention, the crosslinking time is 15 to 20 minutes.

[0011] As a further aspect of the present invention: the process of connecting sequentially from top to bottom is as follows: A pressure-assisted method was used to tightly bond a porous zinc electrode layer and a laser-induced graphene layer to both ends of a polyacrylamide cellulose-based hydrogel, respectively, to prepare a polyacrylamide cellulose-based hydrogel wet generator.

[0012] A polyacrylamide cellulose-based hydrogel moisture generator, prepared by the above method, comprises: It includes a porous zinc electrode layer, a polyacrylamide cellulose-based hydrogel layer, and a laser-induced graphene electrode layer connected sequentially from top to bottom.

[0013] As a further aspect of the present invention, the thickness of the polyacrylamide cellulose-based hydrogel layer is 0.4 to 0.5 cm.

[0014] As a further aspect of the present invention: the polyacrylamide cellulose-based hydrogel wet generator can spontaneously adsorb moisture in the environment for power generation. Under the conditions of 25°C and 60%RH, the open-circuit voltage of a single polyacrylamide cellulose-based hydrogel wet generator reaches 1.92 V and the short-circuit current reaches 2.44 mA.

[0015] The beneficial effects of this invention are: This invention provides a highly hygroscopic hydrogel with a simple and quick preparation method. It can be used as a moisture-absorbing layer in a moisture power generation device to construct a moisture power generation device. Compared with the existing moisture-absorbing layers in moisture power generation devices, the polyacrylamide cellulose-based hydrogel in this invention has a simpler preparation process, better tensile properties, and higher power generation efficiency. This invention provides a polyacrylamide cellulose-based hydrogel wet generator that is simple to prepare, provides continuous and stable power generation, and has a high current density output. This wet generator can continuously generate electricity using ambient moisture, and features high current and voltage output, sustainable and stable operation, environmental friendliness, and all-weather power generation. By vertically arranging a polyacrylamide cellulose-based hydrogel containing a large number of hydroxyl, carboxyl, and amide groups, an ion concentration gradient is formed in the hydrogel after moisture enters. Driven by this concentration gradient, ions migrate in a directional manner, thereby generating an open-circuit voltage. It can continuously generate an open-circuit voltage of 1.9 volts and output a short-circuit current of up to 2.4 mA. Furthermore, a single honeycomb-like hydrogel wet generator can output a short-circuit current density of up to 2.4 mA cm⁻² in an environment with a relative humidity of 60%, exceeding most previously reported wet generators. The polyacrylamide cellulose-based hydrogel wet generator can power many commercial electronic devices, offering significant environmental and economic benefits. It is of great importance to global carbon neutrality efforts and the development of green energy, and possesses significant technological potential. The wet generator of this invention features high voltage and high current density output. A single polyacrylamide cellulose-based hydrogel wet generator can output a short-circuit current density of up to 2.44 mA cm⁻² in an environment with a relative humidity of 60%. This is because the hydrogel contains a large number of hydroxyl, carboxyl, and amide groups, giving it strong water absorption and ionization capabilities. After absorbing water, numerous functional groups effectively dissociate and release a large number of positively charged protons. Simultaneously, during the interaction with water molecules, lithium ions induce the Hofmeister effect, thereby disrupting the hydrogen bonds between water and polymer chains and expanding the ion transport channels between polymer chains. This increases ionic conductivity, facilitating rapid directional migration of charge carriers, thus generating a high current output. The wet generator in this invention has continuous voltage and current output and can maintain a stable state for a long time. A single 1 cm2 wet generator exposed to air can continuously generate a voltage of more than 1 volt for a month and can be used as a power source to power electrical appliances such as light bulbs and calculators through series, parallel and other methods. This invention enhances the mechanical strength of a hydrogel by incorporating a polyacrylamide cellulose-based hydrogel layer and adding lithium chloride, allowing a single polyacrylamide cellulose-based hydrogel to be stretched vertically to 5-6 times its original length. The polyacrylamide cellulose-based hydrogel exhibits excellent mechanical properties. Attached Figure Description

[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a structural diagram of a polyacrylamide cellulose-based hydrogel wet generator disclosed in one embodiment of the present invention; Figure 2 This is a schematic diagram of the principle of the polyacrylamide cellulose-based hydrogel wet generator disclosed in this invention; from top to bottom, the diagram shows the process of functional group ion dissociation; formation of ion concentration gradient; and directional ion migration. Figure 3 This is a Hofmeister Schematic diagram of lithium ions in a wet generator according to an embodiment of the present invention. Figure 4 The Fourier transform infrared spectrum of the polyacrylamide cellulose-based hydrogel in this embodiment of the invention; Figure 5 The in-situ infrared spectrum of the polyacrylamide cellulose-based hydrogel in this embodiment of the invention is shown after 5 hours. Figure 6 This is a long-term test graph of the voltage performance of the wet generator in an embodiment of the present invention; Figure 7 This is a schematic diagram showing the open-circuit voltage and maximum short-circuit current of the polyacrylamide cellulose-based hydrogel wet generator under different humidity conditions disclosed in this invention. Figure 8 This is a schematic diagram showing the open-circuit voltage and maximum short-circuit current of the polyacrylamide cellulose-based hydrogel wet generator disclosed in this invention at different temperatures. Figure 9 This is a schematic diagram of the parallel connection of the voltage of the wet generator in an embodiment of the present invention; Figure 10 This is a schematic diagram of the series connection of the voltage of the wet generator in an embodiment of the present invention. Detailed Implementation

[0018] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0019] Example 1 Please see Figure 1As shown, an embodiment of the present invention provides a polyacrylamide cellulose-based hydrogel wet generator, comprising: a porous zinc electrode layer, a polyacrylamide cellulose-based hydrogel layer, and a laser-induced graphene layer; More specifically, from top to bottom, they are a porous zinc electrode layer, a polyacrylamide cellulose-based hydrogel layer, and a laser-induced graphene layer; The thickness of the polyacrylamide cellulose-based hydrogel layer is 0.4 cm. A single polyacrylamide cellulose-based hydrogel wet generator can be stretched to 5 times its own volume in the vertical direction; This invention provides a method for preparing a polyacrylamide cellulose-based hydrogel wet generator, comprising the following steps: A porous zinc electrode is obtained by punching holes in zinc using a punching tool. The porous zinc electrode has a size of 1*1.5 cm, a hole diameter of about 0.5 mm, and a quantity of 4*4 holes. Laser-induced graphene electrodes were obtained by engraving polyimide films using a laser engraving machine. Acrylamide, carboxylated cellulose, deionized water, and lithium chloride were mixed to obtain a mixed solution, and the mixture was stirred for 30 minutes. Then ammonium sulfate and NN methylenebisacrylamide were added. After stirring for 30 minutes, the resulting solution was poured into a 1cm*1cm*0.5cm silicone mold and placed in a constant temperature and humidity chamber at 60℃ for crosslinking for 15 minutes to obtain polyacrylamide cellulose-based hydrogel. The mass ratio of acrylamide, carboxylated cellulose, deionized water, lithium chloride, ammonium persulfate, and N-N-methylenebisacrylamide is 4:0.14:14:2.8:0.13:0.005. The porous zinc electrode layer, polyacrylamide cellulose-based hydrogel layer, and laser-induced graphene layer are then connected sequentially from top to bottom to form a polyacrylamide cellulose-based hydrogel wet generator.

[0020] Example 2 Please see Figure 1 As shown, an embodiment of the present invention provides a polyacrylamide cellulose-based hydrogel wet generator, comprising: a porous zinc electrode layer, a polyacrylamide cellulose-based hydrogel layer, and a laser-induced graphene layer; More specifically, from top to bottom, they are a porous zinc electrode layer, a polyacrylamide cellulose-based hydrogel layer, and a laser-induced graphene layer; The thickness of the polyacrylamide cellulose-based hydrogel layer is 0.45 cm. A single polyacrylamide cellulose-based hydrogel wet generator can be stretched to 5.5 times its own volume in the vertical direction; This invention provides a method for preparing a polyacrylamide cellulose-based hydrogel wet generator, comprising the following steps: A porous zinc electrode is obtained by punching holes in zinc using a punching tool. The porous zinc electrode has a size of 1*1.5 cm, a hole diameter of about 0.5 mm, and a quantity of 4*4 holes. Laser-induced graphene electrodes were obtained by engraving polyimide films using a laser engraving machine. Acrylamide, carboxylated cellulose, deionized water, and lithium chloride were mixed to obtain a mixed solution, and the mixture was stirred for 30 minutes. Then ammonium sulfate and NN methylenebisacrylamide were added. After stirring for 30 minutes, the resulting solution was poured into a 1cm*1cm*0.5cm silicone mold and placed in a constant temperature and humidity chamber at 60℃ for crosslinking for 18 minutes to obtain polyacrylamide cellulose-based hydrogel. The mass ratio of acrylamide, carboxylated cellulose, deionized water, lithium chloride, ammonium persulfate, and N-N-methylenebisacrylamide is 4.25:0.15:15:3.0:0.135:0.006. The porous zinc electrode layer, polyacrylamide cellulose-based hydrogel layer, and laser-induced graphene layer are then connected sequentially from top to bottom to form a polyacrylamide cellulose-based hydrogel wet generator.

[0021] Example 3 Please see Figure 1 As shown, an embodiment of the present invention provides a polyacrylamide cellulose-based hydrogel wet generator, comprising: a porous zinc electrode layer, a polyacrylamide cellulose-based hydrogel layer, and a laser-induced graphene layer; More specifically, from top to bottom, they are a porous zinc electrode layer, a polyacrylamide cellulose-based hydrogel layer, and a laser-induced graphene layer; The thickness of the polyacrylamide cellulose-based hydrogel layer is 0.5 cm. A single polyacrylamide cellulose-based hydrogel wet generator can be stretched to 6 times its own volume in the vertical direction; This invention provides a method for preparing a polyacrylamide cellulose-based hydrogel wet generator, comprising the following steps: A porous zinc electrode is obtained by punching holes in zinc using a punching tool. The porous zinc electrode has a size of 1*1.5 cm, a hole diameter of about 0.5 mm, and a quantity of 4*4 holes. Laser-induced graphene electrodes were obtained by engraving polyimide films using a laser engraving machine. Acrylamide, carboxylated cellulose, deionized water, and lithium chloride were mixed to obtain a mixed solution, and the mixture was stirred for 30 minutes. Then ammonium sulfate and NN methylenebisacrylamide were added. After stirring for 30 minutes, the resulting solution was poured into a 1cm*1cm*0.5cm silicone mold and placed in a constant temperature and humidity chamber at 60℃ for 20 minutes to crosslink, thus obtaining polyacrylamide cellulose-based hydrogel. The mass ratio of acrylamide, carboxylated cellulose, deionized water, lithium chloride, ammonium persulfate, and N-N-methylenebisacrylamide is 4.5:0.16:16:3.2:0.14:0.007. The porous zinc electrode layer, polyacrylamide cellulose-based hydrogel layer, and laser-induced graphene layer are then connected sequentially from top to bottom to form a polyacrylamide cellulose-based hydrogel wet generator.

[0022] Related tests: The porous zinc electrode and laser-induced graphene electrode of the polyacrylamide cellulose-based hydrogel humidifier obtained in the above embodiments were connected to a Keithley 2400 digital source meter to form a closed-loop circuit, and the generated electrical signal was monitored. It was found that after the polyacrylamide cellulose-based hydrogel humidifier absorbed moisture in air with a relative humidity of 60%, the hydrophilic functional groups on the surface of the hydrogel ionized and dissociated into mobile charged ions. With the humidity gradient on both sides of the hydrogel, the charged ions moved in a directional manner, forming a potential difference, which enabled the polyacrylamide cellulose-based hydrogel humidifier to generate a stable open-circuit voltage.

[0023] Figure 2 This is a schematic diagram of the principle of the polyacrylamide cellulose-based hydrogel wet generator disclosed in this invention. From top to bottom, the diagram shows the processes of functional group ion dissociation, formation of an ion concentration gradient, and directional ion migration. The polyacrylamide cellulose-based hydrogel wet generator disclosed in this invention can continuously generate electricity using moisture in the environment. Because the hydrogel contains a large number of hydroxyl, carboxyl, and amide groups, it has strong water absorption and ionization capabilities. After absorbing water, a large number of functional groups effectively dissociate and release a large number of positively charged protons. Simultaneously, during the interaction with water molecules, lithium ions induce the Hofmeister effect, thereby breaking the hydrogen bonds between water and polymer chains and expanding the ion transport channels between polymer chains. This increases ion conductivity, facilitating rapid directional migration of charge carriers, thus generating a higher current output.

[0024] Figure 3 This relates to the Hofmeister principle of lithium ions in the wet generator in this embodiment of the invention. Due to the high hygroscopicity and the ability of polyacrylamide cellulose-based hydrogel to dissociate a large number of ions (hydroxyl, carboxyl, and amide groups), the polyacrylamide cellulose-based hydrogel wet generator disclosed in this invention achieves high electrical output.

[0025] Figure 4The Fourier transform infrared spectrum of the polyacrylamide cellulose-based hydrogel in this embodiment of the invention is shown. The polyacrylamide cellulose-based hydrogel contains a large number of hydroxyl, carboxyl, and amide groups, which causes the functional group ions in the hydrogel to form an ion concentration gradient after water enters. Driven by the water concentration gradient, the ions undergo directional migration, thereby generating an open circuit voltage.

[0026] Figure 5 The in-situ infrared spectrum of the polyacrylamide cellulose-based hydrogel in this embodiment of the invention is obtained after 5 hours. It can be seen that the strength of hydroxyl and amide groups gradually increases with the increase of water absorption. Figure 6 This is a long-term monitoring curve of the voltage performance of the wet generator in an embodiment of the present invention. Due to the good hygroscopicity and numerous ion transport channels of the hydrogel, the wet generator has a long voltage output duration.

[0027] Performance testing Figure 7 This is a schematic diagram of the open-circuit voltage and maximum short-circuit current of the polyacrylamide cellulose-based hydrogel wet generator disclosed in this invention under different humidity conditions; the polyacrylamide cellulose-based hydrogel wet generator obtained in Example 1 above was placed in environments with relative humidity of 20%, 40%, 60%, and 80% respectively, and the open-circuit voltage and maximum short-circuit current were measured. Figure 8 This is a schematic diagram of the open-circuit voltage and maximum short-circuit current of the polyacrylamide cellulose-based hydrogel wet generator disclosed in this invention at different temperatures; the polyacrylamide cellulose-based hydrogel wet generator obtained in Example 1 above was placed in environments with relative humidity of -20℃, 0℃, 20℃, 40℃, and 60℃, and the open-circuit voltage and maximum short-circuit current were measured. From the above Figure 7 and Figure 8 As shown, under conditions of 25°C and 60% RH, the open-circuit voltage of a single polyacrylamide cellulose-based hydrogel wet generator reaches 1.92 V, and the short-circuit current reaches 2.44 mA. Figure 9 This is a schematic diagram of the parallel connection of the voltage of the wet gas generator in an embodiment of the present invention. The specific steps are as follows: first, a laser engraving machine is used to complete the preparation of a laser-induced graphene array on a PI film; then, the prepared hydrogel and perforated zinc electrode are assembled with the laser-induced graphene by pressure to prepare a parallel array of wet gas generator devices; the measured current obtained by the parallel connection of 90 wet gas generator devices exceeds 90 mA.

[0028] Figure 10This is a schematic diagram of the series connection of the wet gas generator voltage in an embodiment of the present invention. The specific steps are as follows: first, a laser-induced graphene array is prepared on a PI film using a laser engraving machine; then, the prepared hydrogel and perforated zinc electrodes are assembled with the laser-induced graphene under pressure to prepare a series array of wet gas generator devices; the voltage obtained by connecting 60 wet gas generator devices in series exceeds 108 V.

[0029] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A method for preparing a polyacrylamide cellulose-based hydrogel wet generator, characterized in that, Includes the following steps: Porous zinc electrodes are obtained by drilling holes in zinc. Laser-induced graphene electrodes were obtained by engraving polyimide films; Acrylamide, carboxylated cellulose, deionized water, and lithium chloride were mixed to obtain a mixed solution, and the mixture was stirred for 30 minutes. Then ammonium sulfate and NN methylenebisacrylamide were added. After stirring for 30 minutes, the resulting solution was poured into a silicone mold and placed in a constant temperature and humidity chamber for crosslinking to obtain polyacrylamide cellulose-based hydrogel. The porous zinc electrode layer, polyacrylamide cellulose-based hydrogel layer, and laser-induced graphene layer are then connected sequentially from top to bottom to form a polyacrylamide cellulose-based hydrogel wet generator.

2. The method for preparing a polyacrylamide cellulose-based hydrogel wet generator according to claim 1, characterized in that, The porous zinc electrode measures 1*1.5 cm.

3. The method for preparing a polyacrylamide cellulose-based hydrogel wet generator according to claim 1, characterized in that, The hole diameter is 0.5 mm, and the number of holes is 4*4.

4. The method for preparing a polyacrylamide cellulose-based hydrogel wet generator according to claim 1, characterized in that, The mass ratio of acrylamide, carboxylated cellulose, deionized water, lithium chloride, ammonium persulfate, and N-N-methylenebisacrylamide is (4-4.5):(0.14-0.16):(14-16):(2.8-3.2):(0.13-0.14):(0.005-0.007).

5. The method for preparing a polyacrylamide cellulose-based hydrogel wet generator according to claim 1, characterized in that, The cross-linking temperature is 60℃.

6. The method for preparing a polyacrylamide cellulose-based hydrogel wet generator according to claim 1, characterized in that, The cross-linking time is 15 to 20 minutes.

7. The method for preparing a polyacrylamide cellulose-based hydrogel wet generator according to claim 1, characterized in that, The process of connecting sequentially from top to bottom is as follows: A pressure-assisted method was used to tightly bond a porous zinc electrode layer and a laser-induced graphene layer to both ends of a polyacrylamide cellulose-based hydrogel, respectively, to prepare a polyacrylamide cellulose-based hydrogel wet generator.

8. A polyacrylamide cellulose-based hydrogel wet generator, characterized in that, The wet generator is prepared by the method according to any one of claims 1-7, and the wet generator comprises: It includes a porous zinc electrode layer, a polyacrylamide cellulose-based hydrogel layer, and a laser-induced graphene electrode layer connected sequentially from top to bottom.

9. A polyacrylamide cellulose-based hydrogel wet generator according to claim 8, characterized in that, The thickness of the polyacrylamide cellulose-based hydrogel layer is 0.4–0.5 cm.

10. A polyacrylamide cellulose-based hydrogel wet generator according to claim 8, characterized in that, Polyacrylamide cellulose-based hydrogel moisture generators can spontaneously adsorb moisture from the environment for power generation. Under conditions of 25°C and 60% RH, the open-circuit voltage of a single polyacrylamide cellulose-based hydrogel moisture generator reaches 1.92 V, and the short-circuit current reaches 2.44 mA.